2011
DOI: 10.1124/dmd.111.040824
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of In Vitro Rifampin Induction Data Generated in Fresh and Cryopreserved Human Hepatocytes, Fa2N-4, and HepaRG Cells

Abstract: ABSTRACT:Rifampin is a potent inducer of CYP3A4 in vitro and precipitates numerous drug-drug interactions (DDIs) when coadministered with CYP3A4 substrates. In the current study, we have critically assessed reported rifampin in vitro CYP3A4 induction data in Fa2N-4, HepaRG, and cryopreserved or primary human hepatocytes, using either CYP3A4 mRNA or probe substrate metabolism as induction endpoints. An in vivo data base of intravenously administered victim drugs (assuming hepatic induction only) was collated (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…8B). Induction of CYP2B6 in response to indirect activators (i.e., PB and phenytoin) has dmd.aspetjournals.org not been observed with any immortalized hepatic cell lines (i.e., HepG2, Huh-7, Fa2N-4) to date, which has been attributed to insufficient expression and cell-signaling functionality to sequester CAR within the cytosol or translocate it to the nucleus (Sueyoshi et al, 2008;Templeton et al, 2011). CYP2B6 induction in cryo-HepaRG cultures (three independent lots) was further contextualized against the range of responses observed in SC-PHH and showed comparable (and substantially less variable) CYP2B6 induction in response to PB (Fig.…”
Section: Active Uptake Transport Characterizationmentioning
confidence: 99%
“…8B). Induction of CYP2B6 in response to indirect activators (i.e., PB and phenytoin) has dmd.aspetjournals.org not been observed with any immortalized hepatic cell lines (i.e., HepG2, Huh-7, Fa2N-4) to date, which has been attributed to insufficient expression and cell-signaling functionality to sequester CAR within the cytosol or translocate it to the nucleus (Sueyoshi et al, 2008;Templeton et al, 2011). CYP2B6 induction in cryo-HepaRG cultures (three independent lots) was further contextualized against the range of responses observed in SC-PHH and showed comparable (and substantially less variable) CYP2B6 induction in response to PB (Fig.…”
Section: Active Uptake Transport Characterizationmentioning
confidence: 99%
“…Among these alternatives, the human HepaRG cell line is one of the most suitable human hepatic cell lines due to the retention of key liver functionality (Kanebratt and Andersson, 2008;Turpeinen et al, 2009;Templeton et al 2011). This model is considered useful for the evaluation of DDIs as most of the common CYP isoform activities have been measured in this cell line and shown to be both selectively inhibited and induced by prototypical CYP-selective inhibitors and inducers at comparable levels to those of primary cultures of human hepatocytes (Turpeinen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Predictive mathematical models incorporating either induction alone or induction in combination with inhibition mechanisms have been applied by a number of authors (Fahmi et al, 2008b;Shou et al, 2008;Fahmi and Ripp, 2010;Kirby et al, 2011;Templeton et al 2011). Dynamic models based on an inducer concentration-time profile to account for the change in enzyme expression have also been proposed (Almond et al, 2009;Fahmi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the 48-h induction studies (Table 3), DMSO-treated HuH-7 cells showed minimal induction by both rifampicin and dexamethasone compared to HepaRG cells. These results suggested that HuH-7 cells may not be an ideal model for CYP3A4 induction compared with other in vitro models such as primary human hepatocytes and HepaRG cells (Gerets et al 2012; Templeton et al 2011). …”
Section: Discussionmentioning
confidence: 96%